Interface Modulation for the Heterointegration of Diamond on Si - Xing Li; Li Wan; Chaonan Lin; Wen‐Tao Huang; Jing Zhou; Jie Zhu; Xun Yang; Xigui Yang; Zhenfeng Zhang; Yandi Zhu; Xiaoyan Ren; Ziliang Jin; et al. (Advanced Science, 2024)
Abstract Along with the increasing integration density and decreased feature size of current semiconductor technology, heterointegration of the Si‐based devices with diamond has acted as a promising strategy to relieve the existing heat dissipation problem. As one of the heterointegration methods, the microwave plasma chemical vapor deposition (MPCVD) method is utilized to synthesize large‐scale diamond films on a Si substrate, while distinct structures appear at the Si‐diamond interface. Investigation of the formation mechanisms and modulation strategies of the interface is crucial to optimize the heat dissipation behaviors. By taking advantage of electron microscopy, the formation of the epitaxial β‐SiC interlayer is found to be caused by the interaction between the anisotropically sputtered Si and the deposited amorphous carbon. Compared with the randomly oriented β‐SiC interlayer, larger diamond grain sizes can be obtained on the epitaxial β‐SiC interlayer under the same synthesis condition. Moreover, due to the competitive interfacial reactions, the epitaxial β‐SiC interlayer thickness can be reduced by increasing the CH4/H2 ratio (from 3% to 10%), while further increase in the ratio (to 20%) can lead to the broken of the epitaxial relationship. The above findings are expected to provide interfacial design strategies for multiple large‐scale diamond applications.